Design and development of a peristaltic pump for constant flow applications - Ferretti, Patrich; Pagliari, Curzio; Montalti, Andrea; Liverani, Alfredo (Frontiers in Mechanical Engineering, 2023)
In many areas ranging from hydraulics to biomedical to automotive and aerospace there is often a need to move a fluid with a constant flow rate, this is difficult to achieve with any type of pump and usually other elements are inserted to regularize the output. The study was focused on the peristaltic pump because there are few studies on it and it has some interesting features, such as extreme simplicity, small number of components, and extreme compactness of the whole system. The first part of this study is focused on analyzing the classical geometry of the peristaltic pump to understand the origin of the discontinuity in the flow rate; the second part proposes a new geometry that mitigates the flow irregularity by more than 200%. In this way, it is possible to use it in all those sectors where a constant flow rate is required but where insulation between the fluid and the machine is required. Together with the flow study, an analysis of how the main geometric parameters affect the operation of the pump is provided, complete with explanatory graphs and tables. A prototype made through additive manufacturing technologies is also proposed.